Evolution laws and control technology of near and far stress field in hard roof mining roadway - Jie HE; Peng CHENG; Le WU; JunPing FAN (Meitan kexue jishu)
In response to the challenge of controlling deformation and damage in hard roof strong mining roadways, the study, taking the 15119 return airway of Sijiazhuang as an engineering background, employs a comprehensive research methodology combining theoretical analysis, field measurements, numerical simulations, and industrial experiments to investigate the evolution patterns of stress fields in hard roof mining roadways at various distances and the corresponding control techniques.Research indicates that when a 25-meter coal pillar is retained in the mining area of 15119 Hui Feng Lane, the difficulty in collapsing the hard roof causes stress concentration at a distance. Furthermore, this condition exacerbates the deterioration of the near-field stress environment surrounding the roadway during its evolution, which is the underlying issue leading to deformation and failure of the roadway’s surrounding rock.The stress fields of the surrounding rock in roadways exhibit a close interaction; fluctuations in the distant stress field can induce changes in the range and magnitude of the local stress field, thereby affecting the deformation and failure timing and extent of the roadway surrounding rock.Based on this understanding, the principle of regulating both the distant and local stress fields of roadway surrounding rock has been proposed. This involves the effective reallocation of the distribution and transmission pathways of the stress fields through engineering interventions, thereby optimizing the stress environment of the surrounding rock and enhancing the stability of the roadway. Based on the principle, the “pillarless mining with retained wall + roof cutting for pressure relief + enhanced support” method has been proposed to regulate the stress fields both in proximity and at a distance. The new strategy initially adjusts the low-stress zone near the 15119 return airway to 1.5 meters from the adjacent 15117 working face. Subsequently, hydraulic fracturing is utilized to create predetermined fractures in the roof of the 15117 intake airway, thereby controlling the distribution and propagation paths of the far-field stress. Finally, the support for the surrounding rock of the 15119 return airway is strengthened to optimize the near-field stress environment.Industrial trials of the new scheme indicate its efficacy in mitigating the impact of far-field stress on near-field stress. The maximum convergence of the roof and floor in the 15119 return airway, associated with the hydraulic fracturing of the new scheme, is 460 mm, and the maximum rib convergence is 430 mm, resulting in a 26.1% reduction in cross-sectional shrinkage rate. Consequently, the rock surrounding the gallery’s stress control scheme for both far-field and near-field has been proven effective, providing a theoretical basis and technical reference for similar galleries.